Gastric schwannoma: report of two cases and review of the literature. (2018) - Paramythiotis, Daniel; Karakatsanis, Anestis; Pagkou, Diamantoula; Bangeas, Petros; Mantha, Niki; Lypiridou, Sofia; Michalopoulos, Antonis
Highlights: Schwannomas are mesenchymal tumors. Schwannomas are benign, slow-growing and usually asymptomatic tumors, but in some cases bleeding, epigastric pain and palpable mass may occur. Preoperative diagnosis is challenging due to the difficulty of differentiation from other sub-mucosal tumors. The size and location of the tumor, as well as its relation to the surrounding organs, are essential factors in determining the type of operation. Local extirpation, wedge resection, partial, subtotal or even total gastrectomy, are all acceptable operations. Gastric schwannomas have a good prognosis. Abstract: Introduction: Gastrointestinal schwannomas are benign, slow-growing and usually asymptomatic tumors. In some cases bleeding, epigastric pain and palpable mass may be occurring. Preoperative diagnosis is challenging due to the difficulty of differentiation from other submucosal tumors. Diagnosis is most often provided through the histology report. Case presentation: In this study we report two cases of gastric tumors with the suspicion of a GIST preoperatively but histologically confirmed to be gastric schwannomas. Two patients of our study gave to us their written consent for publication. Research work has been reported with the PROCESS criteria. Discussion: Surgical resection should be considered the mainstay of treatment in patients with gastric schwannomas. Possible complications such as bleeding or pyloric stenosis can be presented. The size and location of the tumor, as well as its relation to the surrounding organs, are essential factors in determining the type of resection. Conclusion: Gastric schwannomas are usually presented us submucosal mass. Preoperative diagnosis is challenging due to the difficulty of differentiation from other submucosal tumors. Endoscopic Esophagogastroduodenoscopy with biopsy and endoscopic ultrasound is essential to determine the nature of these lesions. Resection of the lesion in healthy borders is the treatment of choice. Patho-logical examination usually revealed positive S-100 protein and negative CD34, CD117, Actin and desmin strains.